Supply Chain Decisions Considering Micro and Small Retailers’ Financial Constraints and Platform Altruistic Preferences - Wang, Yu (Journal of Global Economy, Business and Finance, 2025)
E-commerce platform as a new type of carrier for data integration and resource allocation has become a key subject of supply chain competition, which can empower small and micro retailers to a certain extent and drive the coordinated development of upstream and downstream of the supply chain. This paper constructs a supply chain composed of brand owners, e-commerce platforms and capital constrained micro and small retailers, considers three kinds of altruistic empowerment of e-commerce platforms with wholesale price, financing and commercial credit period, and analyzes the impact of platform altruistic preference on the ordering of micro and small retailers, the willingness of platform financing, and the performance of the supply chain with capital constraints. The study shows that: micro and small retailers’ ordering volume increases with the platform’s altruistic preference, and the ordering volume of well-funded micro and small retailers under the financing strategy varies inversely with the altruistic preference; e-commerce platforms have a certain degree of willingness to provide financing for relatively fund-constrained micro and small retailers, and considering the risk of default, e-commerce platforms are reluctant to provide commercial credit periods for poorly-funded micro and small retailers; micro and small retailers are more likely to provide commercial credit periods based on the fund The micro and small retailers are more likely to benefit from the financing strategy based on their financial situation and platform altruistic preference; the financing strategy from the altruistic perspective is the preferred strategy for e-commerce platforms. This study provides management insights for platform-based supply chains to rationally formulate altruistic empowerment strategies.